InCl3-mediated addition of indole to isatogens: an expeditious synthesis of 13-deoxy-isatisine A - Kumar, Chepuri V. Suneel; Puranik, Vedavati G.; Ramana, Chepuri V. (Chemistry-A European Journal, 2012)
A strategy directed towards the total synthesis of isatisine A that involves several late-stage metal-catalyzed transformations that address the key carboncarbon and carbonheteroatom bond formations has been developed. As a part of this strategy, methods for the addition of indoles to isatogens that lead selectively to either 2,2-disubstituted N-hydroxyindolin-3-one or 2,2-disubstituted indolin-3-one compounds have been developed by employing InCl3 as a catalyst or as the reagent. The present methods provide the first examples of the additions of indoles to the isatogen nucleus. To demonstrate its viability, the synthesis of 13-deoxy-isatisine A has been completed in ten steps from a known and easily available lactone.
Keywords: indium; indoles; isatogens; Natural products; Total synthesis

Tuning the regioselectivity of gold-catalyzed internal nitroalkyne redox: a cycloisomerization and [3+2]-cycloaddition cascade for the construction of spiro-pseudoindoxyl skeleton - Kumar, Chepuri V. Suneel; Ramana, Chepuri V. (Organic Letters, 2014)
A simple domino process for the construction of the tricyclic core present in the spiro-pseudoindoxyl natural products has been developed. This involves two intramolecular events: the Au-catalyzed nitroalkyne redox leading to isatogen and its subsequent [3 + 2]-cycloaddition with a suitably positioned olefin. The option to modulate the size of the spiro-annulated ring, which is an important variable in this class of natural products, has been explored. Overall, this process molds a linear precursor into a tricyclic system with complete step, atom, and redox economy.

Ru-catalyzed redox-neutral cleavage of the N-O bond in isoxazolidines: isatogens to pseudoindoxyls via a one-pot [3+2]-cycloaddition/N-O cleavage - Kumar, Chepuri V. Suneel; Ramana, Chepuri V. (Organic Letters, 2015)
A novel metal-catalyzed oxygen atom transfer reaction onto olefins is reported. By taking isatogens as substrates, a one-pot [3 + 2]-cycloaddition of nitrone with olefins followed by the Ru-catalyzed redox-neutral N-O bond cleavage of intermediate isoxazolidine has been executed as a simple method for the synthesis of 2,2-disubstituted pseudoindoxyls.

Design and synthesis of C-α-D-mannopyranoside linked mesoporous silica nanoparticles - Nechooli, Hemanth K.; Ramtenki, Vilas; Kumar, Chepuri V. Suneel; Prasad, V. B. L.; Ramana, V. Chepuri (Journal of Chemical Sciences, 2025)
Mannose functionalized mesoporous silica nanoparticles (MSNs) offer a promising approach for developing more targeted, effective, and safer cancer therapies. For many of the applications, immobilization of carbohydrates like mannose onto MSNs is a crucial aspect, and in most cases, mannose moieties are connected through O-glycosidic linkages that are susceptible to acidic/enzymatic hydrolysis. To generate a stable mannose-functionalized MSN, we designed a novel C(14)-alpha-mannosylated tetradeca-1-yne. The key steps involved in the synthesis of C-mannosylated alkyne are C1-alkynylation of tri-O-acetyl-D-glucal with 1-trimethylsilyl-tetradec-1-yne, followed by stereoselective dihydroxylation and the isomerization of the internal triple bond to a terminal position. This mannose ligand was then immobilized onto azidopropyl-functionalized SBA-15 through the Cu(I)-catalyzed azide-alkyne click (CuAAC) reaction. Various physical techniques such as low-angle powder XRD, N-2 adsorption isotherms (BET), Fourier transform infrared (FTIR), high-resolution transmission electron microscopy (HRTEM), field emission scanning electron microscopy (FE-SEM), and thermogravimetric analysis (TGA) have been employed to characterize this C-mannosyl SBA-15 silica matrix. We evaluated the binding ability of C-mannosyl SBA-15 nanoparticles by using fluorescein-labelled Con-A as a target protein.
Keywords: C-mannoside; Click reaction; mannose specific proteins; Mesoporous silica nanoparticles; Zipper reaction